Multi criteria decision making approaches for green supplier evaluation and selection: a literature review. (1st July 2015) - Govindan, Kannan; Rajendran, Sivakumar; Sarkis, Joseph; Murugesan, P.
Abstract: A large and growing body of literature to supplier evaluation and selection exists. Literature on green supplier evaluation that considers environmental factors are relatively limited. Recently, in supply chain management decision making, approaches for evaluating green supplier performance have used both qualitative and quantitative environmental data. Given this evolving research field, the goal and purpose of this paper is to analyze research in international scientific journals and international conference proceedings that focus on green supplier selection. We propose the following questions that will be answered: (i) which selection approaches are commonly applied?, (ii) what environmental and other selection criteria for green supplier management are popular?, (iii) and what limitations exist? Published research from 1997 to 2011 is structurally reviewed based on the first two questions. We find that the applied techniques are mostly fuzzy based single model approaches. The most common criterion considered for green supplier selection was "environmental management systems". A further critical analysis is completed and gaps in the current literature are identified. These gaps help us to identify improvements for green supplier selection process and possible future directions.